2005
DOI: 10.1177/000313480507101206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Tensiometer to Provide Objective Feedback in Knot-Tying Performance

Abstract: Training and assessment methods for knot tying by medical students or residents have traditionally been subjective. Objective methods for evaluating creation of a tied knot should include assessing the strength and quality of the knotted suture. The purpose of this study was to evaluate the use of a tensiometer as a feedback device for improving knot-tying performance. Twelve medical students with no knot-tying experience were selected to perform three-throw instrument ties with 00 silk suture. Students were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 8 publications
(7 reference statements)
1
23
0
Order By: Relevance
“…The selection of the suture material is based on a number of factors involving desirable longevity, anatomical location of the suture site, and the nature and mechanical properties of the tissues being sutured . Knot strength is also a major factor in suture selection, as it will enhance the security of the knot and maintain the desirable wound tension . In dentistry the existence of saliva, bacterial byproducts, and plaque accumulation affects the dimensional stability and mechanical properties of the suture material, compared to dry and isolated wounds of the body .…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the suture material is based on a number of factors involving desirable longevity, anatomical location of the suture site, and the nature and mechanical properties of the tissues being sutured . Knot strength is also a major factor in suture selection, as it will enhance the security of the knot and maintain the desirable wound tension . In dentistry the existence of saliva, bacterial byproducts, and plaque accumulation affects the dimensional stability and mechanical properties of the suture material, compared to dry and isolated wounds of the body .…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical testing of laparoscopic suturing demonstrated that roughly 50% of the suture failures resulted from slipping or unraveling of the knots. 2,3 Efforts have been made to improve…”
Section: Introductionmentioning
confidence: 99%
“…It is based on previously validated cognitive models of human performance learning showing that the individual speed-precision strategies of novices, which occur spontaneously and unconsciously [2,22,24,25], can seriously compromise precision learning at all further stages of training if they are not controlled and corrected for as early as possible in the process. In robot-assisted surgical procedures, for example, where the camera moves along with the tool, for example [10][11][12][13][14][15][16] Peer-reviewed version available at Information 2018, 9, 316; doi:10.3390/info9120316 decision model for unsupervised training procedures of the kind proposed here in this article could also be adapted to such performance criteria on the basis of device-specific expert performance benchmark data.…”
Section: Discussionmentioning
confidence: 99%
“…Benchmarking individual levels of proficiency on the performance levels of experts on a validated metric-based simulation system has well-established intrinsic face validity [9] and appears a better approach than benchmarking on some abstract performance concept based on expert consensus, for example. Building expert performance as a basis for skill assessment into simulator training programs ensures that the "pass" level is defined on realistic criteria set directly by the proficiency levels of individuals who are actually very experienced at performing the actual clinical procedure [9][10][11][12][13]. Artificial intelligence provides well-suited concepts for reinforcement learning procedures and allows building prior benchmark knowledge on expert performance into simulator training most effectively.…”
Section: Of 13mentioning
confidence: 99%